Atsaru al-‘Alāqah baīna Hifdzi al-Qur’ān wa Hifdzi al-Mufradāti Thullāb Madrasah al-Qur’ān al-Tsānawiyyah - Mazidatulfaizah Mazidatulfaizah (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2019)
Abstract The purpose of this study is to uncover the greatness of the Qur'an by knowing whether or not the influence of memorization of the Koran in improving the ability to memorize Arabic vocabulary. The researcher uses a quantitative approach, and the methodology is the experimental causality approach. The researcher chose the students of Madrasah Aliyah Madrasatul Qur'an Tebuireng Jombang as the data source because this school is recognized for their students' achievements in memorizing the Qur'an. Data collection methods used were honest and reliable questionnaire. The results of this study are as follows: 1) Analysis of data obtained from the results of the study showed that the level of memorization of the Qur'an is in the middle level. 2) Analysis of the data obtained from the results of the study shows that the ability to memorize vocabulary is in the middle level. 3) Tahfizh Al-Quran influences the ability to memorize Arabic vocabulary, as evidenced by the distribution of 21% and the rest is influenced by other variables. Keywords: Tahfizh al-quran, Vocabulary, Arabic Abstrak Tujuan dari penelitian ini adalah untuk menyingkap kehebatan al-Quran dengan mengetahui ada atau tidaknya pengaruh hafalan al-Quran dalam meningkatkan kemampuan menghafal kosa kata Bahasa Arab. Peneliti menggunakan pendekatan kuantitatif, dan metodologinya adalah pendekatan kausalitas eksperimen. Peneliti memilih siswa sekolah Madrasah Aliyah Madrasatul Qur’an Tebuireng Jombang sebagai sumber data karena sekolah ini telah terkenal dengan prestasi siswa mereka dalam menghafal Alquran. Metode pengumpulan data yang digunakan adalah tes angket kejujuran dan reliabilitas. Hasil penelitian ini adalah sebagai berikut: 1) Analisis data yang didapat dari hasil penelitian menunjukkan bahwa tingkat hafalan Alquran dalam level menengah. 2) Analisis data yang diperoleh dari hasil penelitian menunjukkan bahwa kemampuan menghafal kosakata adalah dalam level menengah. 3) Terdapat pengaruh tahfizh Al-Quran terhadap kemampuan menghafal kosa kata bahasa Arab, terbukti dengan distribusi 21% dan sisanya dipengaruhi oleh variabel lain. Kata kunci: Tahfizh al-quran, Kosa kata, Bahasa Arab